Studi of Environmental Optimum for Pearl Oyster (Pinctada maxima) Aquacuolture Using Marine GIS and Remote Sensing Case Study of Buleleng Regency, North Bali, Indonesia - Mohan Budiman; Takahiro Osawa; I Wayan Arthana (Graduate Study of Environmental Sciences, Postgraduate Program of Udayana University, 2018)
Oyster aquaculture is one of priorities for development and promotion of aquaculture activities in Buleleng Regency and since 2010 the production always increase and supports coastal communities. The selection of aquaculture structure system and farm site are importance. The selection should be based on an appraisal of the life history, habits, environmental parameters and socio-infrastructure. This study focused on obtaining the aquaculture structure system and site selection for Pearl Oyster (Pinctada maxima) in Buleleng Regency with seven attributes Chl-a, SST, bathymetry, and currents, distance to town, distance to pier, and distance to laboratory. The model structure for identifying culture structure and suitable sites for oyster aquaculture in coastal of Buleleng Regency was built on MCE (Multi Criteria Evaluation), the final result for suitable site outputs were compared with pearl production in Buleleng Regency in 2009, 2010, and 2011. The result of this study is that most areas at Buleleng coastal had medium suitability scores.